KONSUMSI PANGAN DAN STATUS GIZI PADA PENDUDUK ASLI DI KALIMANTAN TIMUR: PENDEKATAN SOSIAL-BUDAYA, DAN EKONOMI - Suhaimi, Ahmad (Lembaga Penelitian Universitas YARSI, 2007)
This study was aimed to examine food consumption and nutritional status in the household of indigenous people ?Dayak? which resided at the low line of Mahakam river, and to conduct the study on social, culture, and economic factors which affected the food consumption. The result showed that average energy and protein consumption per person was 2.000,7 kcal and 71,0 gram which the actual energy consumption level was 100,04% and actual protein consumption level was 136,5%. The value of actual energy consumption level was in the good category (( 100% of RDA) and actual protein consumption level was in the good category ( 100% of RDA). When the nutritional status of children under five was related to energy consumption level of household, the prevalence of malnutrition was in the low and deficit category and the good nutritional status tended to be in the sufficient and good category. The estimation was also supported by the Pearson Correlation of p=0.0001 and r=0.692. Highly significant relationship of nutritional status of children under five and the energy consumption level of household was observed. The socio-culture, economic factors which affected food consumption of household were: nutritional awareness of mother (p=0.016), food preference (p=0.023), food avoidance (p=0.000), inequality of member in the household (p=0.000), and income level of household (p=0.001).